2011
DOI: 10.1074/jbc.m111.243998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Early EDEM1 Protein Maturation Events and Their Functional Implications

Abstract: The endoplasmic reticulum (ER) quality control factor EDEM1 associates with a number of ER proteins and ER-associated degradation (ERAD) substrates; however, an understanding of its role in ERAD is unclear. The early maturation events for EDEM1 including signal sequence cleavage and glycosylation were analyzed, and their relationship to the function of EDEM1 was determined. EDEM1 has five N-linked glycosylation sites with the most C-terminal site recognized poorly cotranslationally, resulting in the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…However, we observed that MNS5 can promote the demannosylation of the N-glycan from GFP glyc -HDEL. In mammals, recent data propose the occurrence of soluble and membrane-bound forms for EDEM1, which might have distinct functions in ERAD (Tamura et al, 2011). Whether such variable protein topologies exist for MNS4 and MNS5 remains to be shown in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that MNS5 can promote the demannosylation of the N-glycan from GFP glyc -HDEL. In mammals, recent data propose the occurrence of soluble and membrane-bound forms for EDEM1, which might have distinct functions in ERAD (Tamura et al, 2011). Whether such variable protein topologies exist for MNS4 and MNS5 remains to be shown in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the literature supports the role of mannose trimming from misfolded proteins as critical to their recognition for ERAD, one cannot overlook the fact that much of the ERAD quality control machinery, including EDEM1, OS-9, XTP3-B, and SEL1L, are themselves N-glycosylated. Because the removal of mannose units from their N-glycans is required for ERAD (24,57), one should consider in future studies that treatment with KIF might actually function by inhibiting critical ERAD associations with SEL1L (24,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…EDEM1 (or just EDEM in earlier reports) has homology to class I α-1,2-mannosidases (which constitute the glycosyl hydrolase family 47). EDEM1 can give rise to soluble and membrane forms because of its inefficiently cleaved ER signal sequence 123,124 . As with ERManI, the role of EDEM1 varies depending on the substrate examined.…”
Section: Glycan-directed Erad In Mammalsmentioning
confidence: 99%